Rational Construction of an Exceptionally Stable MOF Catalyst with Metal‐Adeninate Vertices toward CO2 Cycloaddition under Mild and Cocatalyst‐Free Conditions - He, Hongming; Zhu, Qian‐Qian; Zhao, Jia‐Nan; Sun, Hongming; Chen, Jing; Li, Cheng‐Peng; Du, Miao (Chemistry : a European journal, 2019)
CO2 is considered as the primary greenhouse gas, resulting in a series of serious environmental problems that affect people's life and health. Carbon capture and sequestration has been implemented as one of the most appealing pathways to control and use CO2. Here, we rationally integrate various functional sites within the confined nanospace of a microporous metal–organic framework (MOF) material, which is constructed by mixed‐ligand strategy based on metal‐adeninate vertices. It not only exhibits excellent stability but also can efficiently transform CO2 and epoxides to cyclic carbonates under mild and cocatalyst‐free conditions. Additionally, this catalyst shows extraordinary recyclability for the CO2 cycloaddition reaction. Up in frames: An exceptionally stable MOF catalyst with metal‐adeninate vertices has been designed and constructed by a mixed‐ligand strategy, which can transform CO2 and epoxide into cyclic carbonates with high efficiency, under mild and cocatalyst‐free conditions.